PERANAN ADVOKAT DALAM MENYELESAIKAN PERKARA PERDATA BERKAITAN AZAS SEDERHANA, CEPAT DAN BIAYA RINGAN DI PENGADILAN NEGERI SAMARINDA - Endriyanto Endriyanto (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Whereas the legal relationship between the legal aid provider and the client is indicated by the existence of a power of attorney, whereby the client grants the rights and authority to the legal counsel who receives it to do something on behalf of the client. This power of attorney can be given in an authentic deed made before a notary or other officials, a deed under hand, a letter or verbally.Whereas legal aid providers have a very important role in completing civil cases related to the principle of simple, fast and mild costs, namely through a way of peace sought before the civil case is brought before the court. Besides the settlement of civil cases by means of peace it is simpler, faster and less costly, the settlement of cases carried out with peace will also result in outward and inward decisions and relations between the two parties are expected to be established as usual, because in peace there is no losing party or the winning party.However, if the settlement of a civil case outside the court, namely through the way of peace has been taken but still does not bring results, then the civil case will be brought before the court. So the settlement of civil cases through the courts is the last alternative taken by the parties. As for the efforts made by legal aid providers in court so that the case is resolved in a simple, quick and low cost is to find out the case that he actually bought, prepare the files that will be needed in court, prepare witnesses and in court before the court, Legal aid providers / legal advisors only state the main matters relating to the case they have bought, without having to be long-winded.